Examining the Effect of Anterior Drawer and Lachman Test on Lysholm Score in Patients with Anterior Cruciate Ligament Reconstruction Using Hamstring Tendon - Sadoni, Hanon (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: Anterior cruciate ligament (ACL) tear is a common knee ligament injury with severe complications such as restriction and instability in movement and disability. Arthroscopic reconstruction using hamstring tendon is a common therapeutic option. The outcome of ACL tear surgery is assessed by anterior drawer and Lachman tests where positive scores indicate the failure of the surgery. The present study aimed to assess the positivity of anterior drawer and Lachman tests on knee score of the patients underwent ACL tear surgery and to evaluate the relationship between the positivity of the tests with Lysholm score. Materials and Methods: The present study was conducted on 101 patients with ACL tear. The patients were treated with hamstring tendon using arthroscopic Endobutton fixation. The patients were evaluated with Lysholm score at the 3rd and 9th month post-surgery using anterior drawer and Lachman tests. Positivity of the first two tests was evaluated at the 3rd and 9th month. Lysholm score was also evaluated at the 3rd and 9th month. The changes in the scores of the two tests were compared Results: Anterior drawer and Lachman tests showed gradual positivity at the 3rd and 9th month follow-up examinations. However, the changes in the Lysholm score were not significant. Moreover, patients’ satisfaction and their return to routine activities did not change significantly. The anterior drawer test showed greater changes compared with the Lachman test score. Conclusion: Our findings showed that the outcomes of the anterior drawer and Lachman test did not reliably ensure success of the surgery or patients’ satisfaction and returned to the daily routine work. Lysholm score should also be taken into account in this regard.